Practitioner perceptions of the health of Australian First Nations' Peoples: Preliminary findings. (30th July 2020) - Crouch, Alan; Chew, Bonnie; Freeman, Gwenda
Abstract: Objective: To probe health practitioner perceptions of Australian First Nations' Peoples' health and to compare these with reported burden of disease, social determinants and culturally safe health systems data. Design: An online survey tool was used to collect self‐reported responses from health practitioners to answer literature‐derived questions regarding underlying issues in Australian First Nations' Peoples' health. Setting: Responses to the survey were sought from rural and urban health service locations across all Australian states and territories. Participants: Allied health, nursing, pharmacy, psychology, social work and related discipline students and practitioners currently working or studying in Australia. Main outcome measure(s): Degrees of correspondence between health discipline student and practitioner perceptions on 'major health issues' and 'health systems issues' and published population health and health systems data. Metrics for 'connectedness to' and 'preparedness to engage with' Australian First Nations' Peoples were also reported. Results: Significant differences between practitioner perceptions of 'major health issues' and the disease burden/social determinants published evidence, and with the 'culturally safe health systems' published evidence, were noted. Positive impacts of social and professional relationships (connectedness) between practitioners and First Nations' Peoples were demonstrated. Conclusions: The inclusion of basic population health and culturally safe health systems training in curricula for all genres of health practitioners appears to be indicated by these findings. Further, a meaningful role for the intentional nurture of social and professional relationships with Australian First Nations' Peoples across all health disciplines is suggested as part of efforts to address health systems and equity issues.